“Tetap Fokus di Jalan” : Aesthetic Perspective of Public Service Advertising - Shafira Yuna Azzahra; Muhammad Fikri Alwani; Salsa Solli Nafsika (Universitas Pendidikan Indonesia, 2021)
Based on research data from the World Health Organization (WHO) in 2018, annually, there are around 1.3 million people in the world experienced traffic accidents where one of the factors that has recently increased is due to driving while using cellphones. With the increase in the issue, there is a need for socialization of the dangers that can be caused by driving while using cellphones. “Tetap Fokus di Jalan” is a public service advertisement film that is mean to be a socialization effort of the issue. However, as a work of art that is intended to be effective in proclaiming the social message that the creator wants to convey, an aesthetical theory approach is needed in the process of its creation. DeWitt H. Parker advocates the existence of six principles of an artwork to be declared as a beauty. In this study, the authors uses the aesthetic theory of DeWitt H. Parker to the process of creating the public service advertisement film “Tetap Fokus di Jalan”.